Levels of Athletic Satisfaction of Nour Al-Messila Wheelchair Basketball: A Field Study on the Nour Al-Messila Wheelchair Basketball Team - Amenellah, rachid; BENSALEM, salem (sports creativity, 2025)
 There are groups in society that we try not to look at or interact with, and we pay them no attention, considering them useless, and this is the group of people with disabilities. Although they are humans like us, society has neglected them and buried them in their lives.  Despite the care, attention, and support that the Algerian state has provided to this group of society through enacting laws that protect them, and emphasizing the establishment of institutes and programs for people with disabilities to train and educate them using methods and means suitable for their condition according to their physical and mental abilities, and employing qualified staff to serve this group of society; thanks to this policy, the Ministry of Youth and Sports has sought to direct direct attention to this group and provided the specific resources and needs for people with disabilities. Alongside this and continuing this role, sports clubs and associations specifically for this group have been opened in most of the provinces of Algeria. Among the most important achievements and experiences in the field of sports is the integration of people with disabilities into sports clubs. In this area, we can reach goals that other fields have failed to achieve.  In reality, a person with disabilities seeks through joining a sports club to fulfill their needs  There are various reasons, including the desire to belong to a group that shares the same ambitions or to satisfy one's desires and assert one's existence by achieving the goals set by the sports team under whose banner they operate; these needs are only fulfilled if the individual is satisfied with their role during team activities.  Satisfaction with one's role in team sports is considered a psychological concept that has not received sufficient attention in training and competitions in our country, despite its important and active role in reducing the occurrence of negative effects on team cohesion during training and competition periods.  Research objectives:  Our research focuses on the importance of role satisfaction among players of the Nur M'Sila wheelchair basketball team and the extent to which this satisfaction affects its members, especially in light of the disabilities they face. Therefore, we deemed it necessary to address key points directly related to our research topic.  To clearly understand this importance, we must define the meaning of role satisfaction, its nature and determinants, as well as its impact on the members of the Nur M'Sila team, considering the disabilities they experience and reviewing experts' perspectives on the importance of role satisfaction at all levels. And especially among people with disabilities. This study came to present to researchers the importance of this topic, which calls for significant attention to provide scientific psychological studies in the field of role satisfaction, particularly among people with disabilities, in order to improve their performance, as well as to integrate this group into society by understanding the difficulties they face and delving deeper into the psychological issues they struggle with, and attempting to address them by identifying the factors that help them achieve satisfaction with their role in the team they belong to, thereby achieving their goals.